Observation and mass measurement of the baryon Xib-. - Aaltonen, T; Abulencia, A; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; et al. (2007)
We report the observation and measurement of the mass of the bottom, strange baryon Xi(b)- through the decay chain Xi(b)- -->J/psiXi-, where J/psi-->mu+mu-, Xi- -->Lambdapi-, and Lambda-->ppi-. A signal is observed whose probability of arising from a background fluctuation is 6.6 x 10(-15), or 7.7 Gaussian standard deviations. The Xi(b)- mass is measured to be 5792.9+/-2.5(stat) +/- 1.7(syst) MeV/c2.